Male-biased sex ratios in Australian migrant populations: a population-based study of 1 191 250 births 1999–2015. (23rd July 2018) - Edvardsson, Kristina; Axmon, Anna; Powell, Rhonda; Davey, Mary-Ann
Abstract: Background: The naturally occurring male-to-female (M/F) ratio at birth is 1.05. Higher ratios found primarily in countries across Asia have been attributed to prenatal sex selection due to son preference. There is growing evidence that sex-selective practices continue following migration; however, little is known about these practices following migration to Australia. Methods: In this population-based study we assessed M/F ratios at birth per mother's country of birth for all registered births 1999–2015 in Victoria, Australia ( n = 1 191 250). We also compared the M/F ratio among births to mothers born elsewhere to that of mothers born in Australia, stratified by time period and parity. Results: Compared with the naturally occurring M/F ratio as well as to the M/F ratio among births to mothers born in Australia, there was an increased ratio of male births to mothers born in India, China and South-East Asia, particularly at higher parities and in more recent time periods (elevated M/F ratios ranged from 1·079 to 1·248, relative risks of male birth ranged from 1·012 to 1·084 with confidence intervals between 1·001 and 1·160 and P -values between 0·005 and 0·039). The most male-biased sex ratios were found among multiple births to Indian-born mothers, and parity of two or more births to Indian and Chinese-born mothers in 2011–15. Conclusions: The male-biased sex ratios observed in this study indicate that prenatal sex selection may be continuing following migration to Australia from countries where these practices have been documented. The excess of males among multiple births raises the question as to what role assisted reproduction plays. Findings also suggest that systematic discrimination against females starts in the womb.